Type 1 regulatory T cell-mediated tolerance in health and disease - Freeborn, Robert A.; Strubbe, Steven; Roncarolo, Maria Grazia (Frontiers in Immunology, 2022)
Type 1 regulatory T (Tr1) cells, in addition to other regulatory cells, contribute to immunological tolerance to prevent autoimmunity and excessive inflammation. Tr1 cells arise in the periphery upon antigen stimulation in the presence of tolerogenic antigen presenting cells and secrete large amounts of the immunosuppressive cytokine IL-10. The protective role of Tr1 cells in autoimmune diseases and inflammatory bowel disease has been well established, and this led to the exploration of this population as a potential cell therapy. On the other hand, the role of Tr1 cells in infectious disease is not well characterized, thus raising concern that these tolerogenic cells may cause general immune suppression which would prevent pathogen clearance. In this review, we summarize current literature surrounding Tr1-mediated tolerance and its role in health and disease settings including autoimmunity, inflammatory bowel disease, and infectious diseases.